Sistem Informasi dan Analisis Data Curah Hujan Kota Bandar lampung - Zakaria, Ahmad; Didik, Didik; Algifari, Habib (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2013)
Hydrological data especially rainfall data that observed, often not available, in the otherwords there are missing data. Unavailability of complete data becomes an important prob-lem for the next data processing. Lost data will reduce information that consist in data.There is no a media service access on collect rainfall data with easily and quickly becomes ahomework that must be completed. For help access and processing rainfall data, it's impor-tant to developed "Information systems and analysis daily rainfall data of bandar lampungcity". This system is purpose to provide data and handle rainfall data process.